C9orf72 Hexanucleotide Repeat in Huntington-Like Patients: Systematic Review and Meta-Analysis - Alva-Diaz, Carlos; Alarcon-Ruiz, Christoper A.; Pacheco-Barrios, Kevin; Mori, Nicanor; Pacheco-Mendoza, Josmel; Traynor, Bryan J.; Rivera-Valdivia, Andrea; Lertwilaiwittaya, Pongtawat; Bird, Thomas D.; Cornejo-Olivas, Mario (Frontiers in Genetics, 2020)
Introduction: Patients with Huntington-Like disorders (HLD) comprise a variety of allelic disorders sharing a Huntington phenotype. The hexanucleotide repeat expansion of the C9orf72 gene could explain part of the HLD etiology. We aimed to conduct a systematic review and meta-analysis looking for the frequency of the hexanucleotide repeat expansion of the C9orf72 gene in HLD patients. Methods: The protocol was registered on the International Prospective Register of Systematic Reviews database (PROSPERO) (registration number: CRD42018105465). The search was carried out in Medline, Scopus, Web of Science, and Embase in April 2018, and updated in July 2020. Observational studies reporting patients with HLD carrying the hexanucleotide repeat expansion in the C9orf72 gene were selected and reviewed; this process was duplicated. The cutoff threshold for considering the hexanucleotide expansion as a pathogenic variant was equal to or >30 G4C2 repeats. Cases with intermediate alleles with 20–29 repeat are also analyzed. Pooled frequency and 95% CI were calculated using random-effects models. Results: Nine out of 219 studies were selected, reporting 1,123 affected individuals with HLD. Among them, 18 individuals carried C9orf72 expansion, representing 1% (95% CI: 0–2%, I2 = 0%) of the pooled frequency. Seven selected studies came from European centers, one was reported at a US center, and one came from a South-African center. We identified five individuals carrying intermediate alleles representing 3% (95% CI: 0–14%, I2 = 78.5%). Conclusions: The frequency of C9orf72 unstable hexanucleotide repeat expansion in HLD patients is very low. Further studies with more accurate clinical data and from different ethnic backgrounds are needed to confirm this observation.